Growth of Chinese kangkong at different concentrations of vermicompost. - Acosta, Jennifer (UPHSI, 2005)
Vermicompost is the part of the earthworm's food that it has not been able to digest. Usually it contains bacteria, enzymes, and remnants of plants and animal manure. This makes it very ideal as medium to plant in. At present, a lot of farmers, agriculturists, researchers and even gardeners are experimenting with the potential of vermicompost to produce better plants and crops. A study was made wherein seeds of Chinese Kangkong were planted to determine the effects of vermicompost on the plant at different concentrations. The growth of the seeds, leaf area, above ground biomass, root length and number of leaves were observed and recorded. The concentrations tested were 100% vermicompost and 0% vermicompost. The seeds were planted in black plastic pots, distributed in a well-lighted area and watered daily. The above ground length of the plants was measured every day with the use of the ruler. Culture lasted for 4 weeks. Results showed greatest increase in length of the Chinese Kangkong was at 100% vermicompost although the roots are longest and leaf number is greatest at 50% vermicompost and the above ground biomass and the leaf area were greatest at 0% vermicompost. However, the differences in these growth parameters were insignificant, because of the short duration of the experiment and the limited number of replicates.